(untitled) (Bangladesh Journal of Zoology, 2013)
Out of 200 urine samples of female out patients from BSMMU hospital, 128 (64%) cases were detected as Escherichia coli positive, 66.67% of cases in summer and 60% in winter. To compare the risks of E. coli infection in summer and winter and also among different age groups, odd ratio (OR) and relative risk (RR) were used as measures of comparative likelihood. The values of both OR and RR were greater than one when the risk of E. coli infection of adults (16-35) was compared with that of middle age (36-50) and old age (51-70) groups. The adults were always at higher risk of UTI by E. coli, and the livelihood of infection was not equal in summer and winter. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14317 Bangladesh J. Zool. 40(2): 231-239, 2012